Localization of Hydrogen Peroxide in Dormant Buds of Resistant and Susceptible Chestnut Cultivars: Changes During Gall Developmental Stages Induced by the Asian Chestnut Gall Wasp (Dryocosmus kuriphilus) - Başak Müftüoğlu; Cevriye Mert (Plants, 2025)
Asian chestnut gall wasp (ACGW) (Dryocosmus kuriphilus Yasumatsu), native to China, is an invasive pest that causes significant economic losses in Castanea species. While some cultivars show full resistance by inhibiting insect development in buds, the underlying defense mechanisms remain unclear. In this study, the accumulation and distribution of hydrogen peroxide (H2O2) were investigated in dormant buds of chestnut cultivars that are resistant and susceptible to D. kuriphilus by using the 3,3′-diaminobenzidine (DAB) staining method. Buds were examined under a stereomicroscope during key stages of pest development, including oviposition, transition from egg to larva, gall induction, and gall development. Baseline levels of H2O2 were detected in all buds; however, these levels varied among cultivars, with resistant cultivars exhibiting lower basal levels. The degree of H2O2 accumulation was found to vary depending on plant–insect interaction, physiological processes, and cultivar-specific traits. Histochemical staining revealed that brown spots indicative of H2O2 accumulation were concentrated in the vascular bundles of leaf primordia and in the apical regions. In resistant hybrid cultivars, the defense response was activated at an earlier stage, while in resistant Castanea sativa Mill. cultivars, the response was delayed but more robust. Although consistently high levels of H2O2 were observed throughout the pest interaction in susceptible cultivars, gall development was not inhibited. During the onset of physiological bud break, increased H2O2 accumulation was observed across all cultivars. This increase was associated with endodormancy in susceptible cultivars and with both defense mechanisms and endodormancy processes in resistant cultivars. These findings highlight the significant role of H2O2 in plant defense responses, while also supporting its function as a multifunctional signaling molecule involved in gall development and the regulation of physiological processes.